AMINO ACID COMPOSITION AND BIOLOGICAL VALUE OF PROTEIN TEXTURES USING UNCONVENTIONAL RAW MATERIALS - CHEPURNA, OKSANA; SHTONDA, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper examines the relevance of creating protein textures using unconventional raw materials. A comparative analysis of the essential amino acids content of the main raw materials was conducted, along with the calculation of the amino acid score and biological value indicators of cereal-soy textured product and soy textured product. The object of research was a cereal-soy textured product in the formulation of which soybean low-fat flour was partially replaced with brewer’s grains flour. Brewer’s grains are a byproduct of the brewing industry that requires disposal to address environmental safety concerns. One possible utilization method is to use brewer’s grains as a protein raw material in the development of new types of food products. An analysis of the raw materials used in the experimental textured products revealed that the lowest content of essential amino acids was observed in defatted soybean flour. Soybean meal, wheat gluten, and brewer’s grain flour have approximately the same amount of isoleucine - 4.1-4.63 g/100 g of protein, methionine+cystine - 2.73-3.51 g/100 g of protein, and threonine - 2.54-3.64 g/100 g. It was established that histidine was the limiting amino acid for cereal-soy textured product and soy textured product, which was used to determine the biological value and degree of protein digestion. The most balanced was cereal-soy textured product, which has a higher protein utilisation factor of 72.16% and biological value of 80.4%, respectively. The obtained value of the amino acid imbalance coefficient for cereal-soy textured product is 19.6%, for soy textured product - 20.7%. The biological value of soy textured product is 79.3%. The data presented in the article allow us to conclude that brewer’s grain is a valuable protein secondary raw material that can be used in food production technologies, particularly in sausage products and meat semi-finished products